Effect of Good Agricultural Practices (GAP) implementation toward yield performances / Farah Natasha Mohamad Sain - Mohamad Sain, Farah Natasha (Faculty of Plantation and Agrotechnology, 2019)
Oil palm is one of the major crop producing in Malaysia. Although there are many oil palm plantation were develop in our country and the productivity may rise but there were still had a problem in term of implement Good Agricultural Practices (GAP) in field that will affecting the quality and quantity of oil palm production. Palm oil industry players such as Rubber Industry Smallholders Development Authority (RISDA), Federal Land Development Authority (FELDA) and the Malaysian Palm Oil Board (MPOB) has implemented various strategies and programs to enhance the production of sustainable palm oil in this country including for dependent smallholders. Survey was conducted by using the simple random sampling method of 75 population of smallholders and distributed among 63 smallholders based on Krejcie and Morgan table at Felcra Sri Mendapat, Melaka. The aim of this research study was to identify the implementation of good agricultural practices (GAP) among dependent smallholders and to determine the relationship of good agricultural practices (GAP) and yield performances. Data was analyzed by using the software Statistical Package for Social Science (SPSS) through descriptive analysis, reliability analysis, correlation analysis and multiple regression analysis. Pearson correlation is use to analyzed the relationship between a few factors such as crop recovery, canopy management and soil, moisture and nutrient management towards yield performances.